History Teachers’ Strategies For Improving Academic Achievement At Kasimbar State Sma Negeri 1 Kasimbar - Magfirah; Haliadi Sadi; Minarni Nongtji; Hasan (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the strategies employed by history teachers to improve students' learning achievement at SMA Negeri 1 Kasimbar. The research employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation involving history teachers and students SMA Negeri 1 Kasimbar as research subjects. Data analysis was conducted using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings reveal that history teachers implemented systematic lesson planning, utilized various teaching methods, employed diverse learning media, and created a conducive learning environment. The teachers applied lecture, question-and-answer, and discussion methods supported by textbooks, internet resources, pictures, videos, and digital media. These strategies contributed to improving students' learning achievement, as indicated by better understanding of historical materials, increased learning motivation and interest, and greater participation in discussions and presentations. Therefore, history teachers' strategies play a significant role in creating effective learning processes and enhancing students' learning achievement at SMA Negeri 1 Kasimbar.